Design, Manufacturing and Analysis of Alloy Steel Brake Disc - Badkar, P. S.; Kalai, D. M. (Asian Review of Mechanical Engineering, 2017)
Each single system has been studied and developed in ordered to meet the safety requirement. Instead of having air bag, good suspension systems, good handling and safe cornering, there is one most critical system in the vehicle which is brake system. Without brake system in the vehicle will put a passenger in unsafe position. Therefore, it is must for all vehicles to have proper brake system. In this paper alloy steel disc brake material use for calculating normal force, shear force and piston force And also calculating the brake distance of disc brake. The standard disc brakes two wheelers model using in ANSYS and done the Thermal analysis and Model analysis also calculate the Heat flux and Temperature of disc brake model. This is important to understand action force and friction force on the disc brake new material, how disc brake works more efficiently, which can help to reduce the accident that may happen in each day.